Numerical investigation of performance and exergy analysis in parabolic trough solar collectors - Ramesh K. Donga; Suresh Kumar; Gurunadh Velidi (Scientific Reports)
Abstract This numerical investigation examines the performance and exergy analysis of parabolic trough solar collectors, focusing on the substitution of the conventional circular absorber with a rhombus-shaped absorber. By evaluating the thermal and fluid dynamics properties, this study aims to identify improvements in overall system performance and efficiency. This numerical study conducts a comprehensive thermal analysis of parabolic trough solar collectors by comparing a rhombus-shaped absorber with a conventional circular absorber. The analysis considers two rim angles of the parabolic trough, specifically 80° and 90°. Fluid flow rates ranging from 200 to 600 L per minute and inlet fluid temperatures spanning from 400 to 650 K are evaluated for each configuration. The objective is to determine the impact of absorber shape, rim angle, flow rate, and inlet temperature on the thermal performance and exergy efficiency of the system. Additionally, a slope error range of 0 to 2.5 mrad is incorporated into the study. The optical efficiency, thermal efficiency, exergy efficiency, and overall efficiency of the parabolic trough solar collector are estimated and compared for both absorber shapes. Results indicate that the thermal performance of the collector improves significantly with the rhombus-shaped absorber, showing maximum increases of 2.88% in thermal efficiency, 1.45% in exergy efficiency, and 1.4% in overall efficiency compared to the conventional circular absorber. These findings provide valuable insights for optimizing the design of parabolic trough solar collectors to enhance their overall efficiency and energy conversion effectiveness.